Correspondance et genèse - Giang-Huong Nguyen (Continents manuscrits)
Within the family archives of Marcelino Truong, renowned illustrator and author of graphic novels, we have found the letters that his maternal grandmother, Madame Denise Horel, received from Pham Duy Khiem concerning the preparation of the novel Nam et Sylvie, in addition to two typed versions of this story. We propose to study this genetic file of Nam et Sylvie and to analyze the final stages in Pham Duy Khiem’s writing process in taking into account the 120 letters the writer sent to his friend and the two typed versions that she saved.